1995
DOI: 10.1098/rspb.1995.0180
|View full text |Cite
|
Sign up to set email alerts
|

Multiple origins of anaerobic ciliates with hydrogenosomes within the radiation of aerobic ciliates

Abstract: Some ciliates live anaerobically and lack mitochondria, but possess hydrogenosomes: organelles that contain hydrogenase and produce hydrogen. The origin of hydrogenosomes has been explained by two competing hypotheses: (i) they are biochemically modified mitochondria; or (ii) they are derived from endosymbiotic association(s) of ciliates and anaerobic eubacteria that possessed the hydrogenosome biochemistry. Phylogenetic analyses of representative aerobic, and anaerobic hydrogenosomal ciliates using host nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(45 citation statements)
references
References 19 publications
2
43
0
Order By: Relevance
“…The ciliate tree is divided in two deep lineages -the Postciliodesmatophora and Intramacronucleata, a split that is supported by both molecular and morphological lines of evidence (BaroinTourancheau et al, 1998;Embley et al, 1995;Gao et al, 2010;Hirt et al, 1995;Lynn, 1996Lynn, , 2003. Beyond this deep division, it is generally agreed that there are 11 major ciliate lineages or classes and a twelfth single species clade of Cariacotrichea (Adl et al, 2012;Lynn, 2008;Orsi et al, 2012;Stoeck et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ciliate tree is divided in two deep lineages -the Postciliodesmatophora and Intramacronucleata, a split that is supported by both molecular and morphological lines of evidence (BaroinTourancheau et al, 1998;Embley et al, 1995;Gao et al, 2010;Hirt et al, 1995;Lynn, 1996Lynn, , 2003. Beyond this deep division, it is generally agreed that there are 11 major ciliate lineages or classes and a twelfth single species clade of Cariacotrichea (Adl et al, 2012;Lynn, 2008;Orsi et al, 2012;Stoeck et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond this deep division, it is generally agreed that there are 11 major ciliate lineages or classes and a twelfth single species clade of Cariacotrichea (Adl et al, 2012;Lynn, 2008;Orsi et al, 2012;Stoeck et al, 2003). Most of these classes are strongly supported by morphology, with the exception of the ''riboclasses'' -the Armophorea and Plagiopylea, which are identified only by sequences of the 18S rRNA genes, as included taxa lack any morphological synapomorphies (Bernhard et al, 1995(Bernhard et al, , 2001Cameron et al, 2001;Embley et al, 1995;Greenwood et al, 1991;Leipe et al, 1994;Lynn, 2008;Lynn et al, 1999;Lynn and Strüder-Kypke, 2002;Snoeyenbos-West et al, 2004;Stechmann et al, 1998). Nevertheless, the monophyly of the class Spirotrichea has been challenged in several studies, notably those that include Protocruzia spp.…”
Section: Introductionmentioning
confidence: 99%
“…The paucity of data has made it difficult to infer the relationships between these organelles and those occurring in trichomonads and anaerobic ciliates. Because hydrogenosomes are found in a broad phylogenetic range of amitochondriate organisms [2-A] it has been suggested that they must have been acquired independently [4]. Hydrogenosomes are a site of substrate-level phosphorylation and are significant energetically for these taxa.…”
Section: Introductionmentioning
confidence: 99%
“…Fax: (31) suggested that hydrogenosomes in anaerobic ciliates and trichomonads are derived from mitochondria [5]. In contrast, fungal hydrogenosomes have been reported to possess only a single membrane [6] giving rise to the hypothesis that microbodies are the progenitor organelles for these particular hydrogenosomes [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation